A FUND–CHANGE–STATEMENT APPROACH TO THE CALCULATION OF INFLATIONARY DISTORTION IN CONVENTIONAL INCOME MEASUREMENT. - Carson, A. B. (The Accounting Review, 1954)
Abstract Efforts to induce accountants to give recognition to the distorting effect of inflation in the financial statements and reports that they prepare have met with little or no successs. Proponents of the inclusion of such information in financial reports might advance their cause more effectively if they joined in the advocacy of steps that do not digress very far from established and conventional practice. It is suggested that such a first step might be the inclusion in financial reports of a com- paratively non-technical, brief explanation of the extent to which inflation has distorted conventionally-calculated net income. Such an explanation might include mention of any loss from the depreciation of net working capital, and any gain from the liquidation of noncurrent liabilities. The source and application of funds statement (if properly amended) will serve to provide many of the figures that need to be adjusted in order to estimate the magnitude of the inflationary-caused distortions of reported operating results. A revision of the statement to exclude inventories and current prepayments from the definition of funds (net working capital is recommended. The results of the computations of the type suggested cannot be regarded as mote than reasonable estimates. Their credibility is less likely to be challenged if they are reported (in round amounts) are no more than this. Accountants who profess to pay allegiance to the principle of full disclosure can do, at least this much.